THE PERFORMANCE OF AFFIRMATIVE ACTION STUDENTS AND ANALYSIS OF SUBJECTS GRADES USING LATENT CLASS AND LATENT BUDGET MODELS - JELIHOVSCHI, Enio Galinkin (Brazilian Journal of Biometrics, 2018)
Latent class analysis (LCA) is used to analyse data about performance of students. The original performance variables in the data set are course grade and approval status. However, those variables were not used directly, instead four new variables were calculated from those previous two, variables which are much more informative about the student performance. Coupled with another variable, say afirmative action, the results give light to an understanding about the performance of the divided by afirmative action, yes or no. Besides of showing the results it is also shown how the changing of the original variables by some suitable transformation of the original ones gives more reliable results. The main result is that armative action students have a lower performance than those coming from private schools. The paper also analyses the subjects grades using latent budget analysis (LBA), and it is found that the variables cited above have a real effect in characterizing the subjects. It is also shown that those results can be used in a process of evaluation on how the subject is being taught.